Gender dan Korupsi (Pengaruh Kesetaraan Gender DPRD dalam Pemberantasan Korupsi di Kota Yogyakarta) - Aroma Elmina Martha; Dwi Hastuti (Jurnal Hukum IUS QUIA IUSTUM, 2013)
Gender Gender and corruption are the recent problems in the anti-graft issue. This research is aimed at understanding the profile and gender equality influence in the corruption eradication attempts in DPRD Kota Yogyakarta. The research uses the combination method between quantitative and qualitative data. The result of the research shows that: First, the aspects of values, state governance ethics, attitude guidance and accountability of women are better than those of men. Women have nine indicators of excellence, while male members of the legislatives only have seven indicators of excellence. However, there is a gender inequality in DPRD Kota Yogyakarta. The large gap of inequality occurs in the control of and benefit for the women in each activity they follow. Second, the superiority of woman in the corruption eradication attempt will not be meaningful without gender equality.